A narrative synthesis of the cost-effectiveness studies of smoking-cessation programmes - Seninde, Ibrah Kato (My University, 2020)
Objectives: Tobacco smoking remains a major public health problem from both health and economic perspectives. Although several studies have assessed the cost-effectiveness of smoking-cessation programmes, no review has estimated their incremental net benefit. This review synthesizes evidence on cost effectiveness of smoking-cessation programmes. Methods: A literature search on cost-effectiveness of smoking-cessation programmes was conducted in the PubMed, EconLit Full-Text and Medline Complete databases. Primary studies were eligible if they conducted cost effectiveness analyses and reported incremental cost effectiveness ratios for smoking-cessation programmes. Incremental net benefits were estimated using country-specific gross national income per capita as a proxy for the willingness to pay threshold. Comparative analyses of incremental net benefit were conducted for low-and middle-income countries and for South Africa. Results: A total of eighteen primary studies were eligible for inclusion in the review. Results show wide variation in the cost-effectiveness of smoking-cessation programmes based on the willingness to pay thresholds. Many of the interventions tailored for developed country contexts would not be economically feasible in low-and middle-income country settings. Conclusion The variations in study designs, outcome measures and settings make comparison difficult and thus a conclusive judgement about the cost effectiveness of smoking-cessation programmes cannot be made. Nevertheless, findings suggest that telephone counselling and pharmacotherapy-based interventions potentially yield higher health and monetary benefits when compared with low resource intensive programmes like self-help manuals; although pharmacotherapies appear relatively costly in low income country settings. This review highlights several shortcomings in methodology and transferability of the results. Efforts to develop statistical measures for pooling cost effectiveness outcomes will benefit future research
A research report submitted in partial fulfilment of the degree of Master of Commerce (Economics) in the School of Economic and Business Sciences, University of the Witwatersrand, 2020